Studi Perencanaan Embung Kembangan Kecamatan Pule Kabupaten Trenggalek Provinsi Jawa Timur - Mahardhika, Tatag Tata; Sisinggih, Dian; Suprijanto, Heri (Jurnal Teknologi dan Rekayasa Sumber Daya Air, 2021)
Kembangan Village in Pule District is a part of Trenggalek Region which have water resources issues including irigation issue and raw water supply issue. This problem happens because the lack of water resources infrastructures. Based on this two issues to it was so importan to design small dams which is placed on Kembangan Village solve the problem. Based on the data and literature, it was recommended to design the small dam by random soil type with vertical core zone. The body of small dam height planned to be design by 13 m (+552 for the elevation), the width was designed by 6 m, the slope of hillside was 1 : 3 for the upstream and 1 : 2.5 for the downstream. Kembangan smalldam using overflow spillway which is equipped with weir typed ogee, transition channel, sloping apron, and stilling basin. The spillway planned to be design by 8 m width with weir height by 2 m. Kembangan small damn have a potential reservoir capacity for 38219.40 m3 to fullfill the irigation and water supply. It was important to analyzing the stability of small dam for the landslide and seepage factors.